2013
DOI: 10.4097/kjae.2013.65.2.142
|View full text |Cite
|
Sign up to set email alerts
|

The impact of remifentanil on incidence and severity of postoperative nausea and vomiting in a university hospital-based ambulatory surgery center: a retrospective observation study

Abstract: BackgroundAmbulatory surgery, including short-stay surgery, has become a common choice in clinical practice. For the success of ambulatory surgery, perioperative care with safe and effective anesthesia and postoperative analgesia, which can reduce the occurrence of postoperative nausea and vomiting (PONV), is essential. The effect of remifentanil on the occurrence and severity of PONV has not been thoroughly examined, particularly, in an ambulatory surgery setting. Here, we investigate whether remifentanil inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…There was no inter-group difference in the incidence of PONV in this study, even though the dose of intraoperative remifentanil in the TIVA + PECSB group was significantly lower than that in the TIVA group. Some studies indicated that doses of both fentanyl and remifentanil during surgery were risk factors for PONV [ 9 , 10 ], but other studies showed that intraoperative remifentanil dose did not correlate with the severity of PONV [ 11 , 12 ]. This study suggests that intraoperative dose of remifentanil may not affect the incidence of PONV.…”
Section: Resultsmentioning
confidence: 99%
“…There was no inter-group difference in the incidence of PONV in this study, even though the dose of intraoperative remifentanil in the TIVA + PECSB group was significantly lower than that in the TIVA group. Some studies indicated that doses of both fentanyl and remifentanil during surgery were risk factors for PONV [ 9 , 10 ], but other studies showed that intraoperative remifentanil dose did not correlate with the severity of PONV [ 11 , 12 ]. This study suggests that intraoperative dose of remifentanil may not affect the incidence of PONV.…”
Section: Resultsmentioning
confidence: 99%
“…Lenz et al [ 43 ] reported that intraoperative remifentanil at high doses (0.3–0.5 µg/kg/min) increased postoperative pain and morphine consumption. Another study reported that remifentanil did not increase the frequency of PONV or the use of analgesics after ambulatory surgery [ 44 ].…”
Section: Intraoperative Anesthetic Managementmentioning
confidence: 99%
“…Dexmedetomidine: Dexmedetomidine is an α-2-adrenoceptor agonist with sedative, anxiolytic, sympatholytic, and analgesicsparing effects while causing minimal depression of respiratory function (Figure 1) [33][34][35][36]. Hemodynamic effects include transient hypertension, bradycardia, and hypotension.…”
Section: Center (Asc)mentioning
confidence: 99%
“…Therefore, it was not practical in bolus application and should only be employed by pump infusion. It was highly suitable for outpatient spine surgery [36].…”
Section: Center (Asc)mentioning
confidence: 99%
See 1 more Smart Citation